Primerjava 2-D in 3-D slik vidnega polja v načinu "threshold" z diferenčno metodo - Ikica, Andrej (Informatica Medica Slovenica, 2005)
In this article we present methods for processing campus data of a patient. The data is received from HFA (Humphrey Field Analyser). HFA works in two modes: threshold and screening mode. We focused our work on threshold mode, where HFA provides numerical values (intensities) of campus. We capture HFA data, process it and display it in 2-D or 3-D space. Possibility to compare different campuses of patients is essential to medical staff. It is a powerfultool for diagnostics. We developed two different methods for comparingcampuses. First is based on comparison of two different images of campus, where difference is computed for every pixel in image. Second method compares image of a campus with an "optimal" surface of campus, campus of an average patient. Optimal surface varies with patient's age, so we have to modify it in a regular way.
Keywords: Diagnosis, Computer-Assisted; diagnostika; Diagnostika z računalnikom; naprave; oftalmologija; Perimetrija; Perimetry; Vidna polja; vidno polje; Visual Fields